Mídia, emoção e cultura gaúcha: a construção da imagem do jornalista Paulo Sant Ana no Rio Grande do Sul - Specht, Patrícia Pivoto (2008)
The new post-modern Zeitgeist of the early 21st century has imagery, impermanence and fragmentation as its hallmarks and requires mediatic relations that include the cultivation of sensory and affective possibilities. The journalist Paulo Sant Ana, 69, native of the state of Rio Grande do Sul and object of the present master s degree dissertation, fits well into this context inasmuch as he follows strategies that have the complexity required by this new reality. Since the 1970s Sant Ana has been active in three communication media of Rio Grande do Sul: the Zero Hora newspaper, Rádio Gaúcha and RBS TV Porto Alegre, which are part of the Rede Brasil Sul de Comunicação, or RBS (Southern Brazil Communication Network), the largest and most powerful media monopoly of the southern region and one of the most important in Brazil. Since September 2007 Sant Ana has had his own blog at www.zerohora.com. With the help of theatrical performances in which he uses jokes, irony and metaphors, he has built over the course of 37 years a style of journalism all his own, something that comes close to a creative post-modernism directly linked to daily life and experiences. Within this sphere, the most important of the two hypotheses of this study, which attempts to understand how the construct of the image of a mediatic phenomenon took place, is that Sant Ana s success can be at least partly explained by his unique and singular way of being and presenting himself as a mediatic subject, who, by means of his doings and manner of presenting himself, creates an identity associated with trustworthiness, honesty, authenticity and sensibility. Based on the premise that every discourse has the hallmarks (styles, beliefs and competencies) of its enunciator, this Master s Degree Dissertation has analyzed the facts (newsworthy or not) that most strongly influenced the definition of this journalist s identity. The other and not less significant hypothesis is that Sant Ana embodies features related to the character of the natives of Rio Grande do Sul, such as courage, pride and magnanimity, that stir the imagination of the natives of this state. To this perspective were added vital reflections on post-modernity, columns, news and regionalism (Harvey, Sodré, Maffesoli, Bauman, Vicchiatti, Chaparro, Oliven, Debord and others), besides the analysis of Sant Ana s discourse undertaken with the instruments of discursive semiotics (Greimas, Oliveira, Landowski, Pessoa de Barros, Fiorin, Fechini and others). The texts that were analyzed and that with, within the semiotic perspective, are not necessarily verbal were chosen from online searches, interviews, analyses of recorded radio and TV programs, as well as bibliographical and newspaper research